SwEDeL: Software Estimates’ Defense Lenses Designed from Negotiation Methods - Matsubara, Patricia Gomes Fernandes; Steinmacher, Igor; Gadelha, Bruno; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
Software organizations face increasing pressure for higher productivity and faster delivery. In this context, technically sound software estimates created by competent software practitioners to account for software risks can be rejected, favoring too aggressive estimates and the unrealistic commitments that arise from them. Then, software teams work under constant time pressure, sacrificing product quality to keep up with the expectations created. Time pressure also leads software practitioners to exhibit emotional distress, decreasing productivity, which leads to more time pressure and delays: a vicious cycle. This work proposes an approach to support software estimators in defending their realistic estimates instead of yielding to pressure over them. We designed a set of defense lenses based on consolidated negotiation principles and presented them through a digital simulation. We evaluated the digital simulation through a controlled experiment with software professionals. We employed the Theory of Planned Behavior to understand the intentions of participants to defend their software estimates, also collecting data on the antecedents of intentions: attitudes, subjective norms, and perceived behavioral control. Our results show that scores for the study variables improved among experimental group participants after participating in the digital simulation. They were more inclined to choose a defense action when facing pressure scenarios than the control group. The participants also perceived the lenses as useful, showing the relevance of the proposed approach. The original paper was published in Matsubara et al. [17].